Planktonic centric diatoms from the Eastern Alps: morphology, biogeography and ecology - Eugen Rott; Werner Kofler (Plant and Fungal Systematics, 2021)
Centric diatoms from 26 lakes along the northern perialpine areas and lower altitude valleys and terraces along the W-E extension of the Eastern Alps (mostly in Austria) were studied with the intention to facilitate taxonomic identification and ecological studies in the context of water quality monitoring according to the Water Framework Directive of the European Community. Eight genera were found: Aulacoseira , Conticribra , Cyclostephanos , Cyclotella , Lindavia , Pantocsekiella , Stephanodiscus , Urosolenia . For more than 30 infrageneric taxa, morphology (light microscopy LM), ultrastructure of frustules (scanning electron microscopy SEM), distribution pattern and ecology were studied. Although most of the morphological and ultrastructural features correspond to earlier findings, some additional observations were recorded and some taxonomic views were critically assessed and commented based on our observations. The most important nomenclature-related updates in recent studies are adapted based on molecular findings in literature (mainly for the genera Lindavia and Pantocsekiella ). The most widely distributed taxa found were small single celled centrics (mainly species of the genera Cyclotella s.str., Lindavia , Pantocsekiella and Stephanodiscus ) dominating frequently in small enriched lakes. In contrast a few larger oligotraphentic single celled (e.g., Lindavia intermedia ) and chain-forming taxa (e.g., Aulacoseira islandica ) were found to be restricted to the large lakes. The evaluation of the taxa pattern by Canonical Correspondence Analysis (CCA) identified trophic status and lake size as the two primary influential environmental variables for taxa distribution within the dataset. The trophic ranking of species is set in relation to earlier studies and indicator lists.